Production of Doubled Haploids in Onion: A Review - A S Dhatt (Society for Promotion of Horticulture - Indian Institute of Horticultural Research, 2014)
Onion suffers from high inbreeding depression and, as a result, inbreds that are developed lack genotypic and phenotypic uniformity. Gynogenesis has emerged as a potential strategy to address this drawback. Efforts have been made since the 1980s for identifying highly-responsive genotypes and for overall improvement of the protocol for bettering gynogenic frequency in onion. Besides improving media composition, identification of responsive explants and increasing the chromosome efficiency has remained a major area of focus over the years. This article purports to review progress made thus far in the induction of gynogenic haploids in onion, and challenges/opportunities associated with it.